2020
DOI: 10.1097/nmd.0000000000001179
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Verbal Hallucinations in Schizophrenia

Abstract: Recent reviews on auditory verbal hallucinations (AVHs) advocate a qualitative and interdisciplinary research that not only is limited to single descriptive features, but also involves contextual issues and co-occurring psychopathology. In this study of mainly readmitted patients with the International Classification of Diseases, Tenth Revision , diagnosis of paranoid schizophrenia and experiencing AVH, we performed a qualitative, phenomenologically oriented interview study. The focus wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The mean temporal interval between the first emergence of anomalous experiences and a full articulation of AVH was 6.5 years. Thus, in 10 of our cases, the hallucinatory experiences began in childhood or adolescence (Yttri et al, 2020). This finding is concordant with the results of the birth-cohort studies reporting that hallucinations at ages 11 and 14, respectively, were highly predictive of adult nonaffective psychosis (Cannon et al, 2002;Welham et al, 2009).…”
Section: Current Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The mean temporal interval between the first emergence of anomalous experiences and a full articulation of AVH was 6.5 years. Thus, in 10 of our cases, the hallucinatory experiences began in childhood or adolescence (Yttri et al, 2020). This finding is concordant with the results of the birth-cohort studies reporting that hallucinations at ages 11 and 14, respectively, were highly predictive of adult nonaffective psychosis (Cannon et al, 2002;Welham et al, 2009).…”
Section: Current Resultssupporting
confidence: 91%
“…Before we proceed with the presentation of the specific results of the study, we will briefly summarize the findings reported previously from the same sample ( Yttri et al, 2020 ). The most striking result was a long delay between the beginning of AVHs and their disclosure to the psychiatric personnel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other psychopathological domains inspired by self-disorder research comprise investigations into the nature of insight into illness in schizophrenia [51], the condition of double bookkeeping [52], and disorders of introspection [53]. Currently, a work is in progress concerning the phenomenology of auditory verbal hallucinations and their potential route in the instability of selfhood [54]. On a theoretical level, we have proposed that psychiatric classification should not only be based on a common sense symptomatic description of disorders, but should also crucially include considerations about the nature of the basic structures of subjectivity [55].…”
Section: Resultsmentioning
confidence: 99%